Calcium-Phosphate Metabolism Disorders in Patients with Renal Failure Clinical Significance, Diagnosis and Treatment - Grozeva V. (Sciendo, 2019)
Chronic kidney diseases (CKD) are commonly associated with calcium and phosphorus metabolism disorders. The general term of “renal osteodystrophy” (ROD) encompasses a complex spectrum of abnormalities in bone and mineral metabolism in CKD. This is one of the most serious and debilitating complications of CKD. It is related to disproportionately high direct and indirect costs of healthcare, thus posing a major burden on society. The development of ROD begins too early in the course of CKD. Some mechanisms involved in the pathogenesis of ROD are reduced calciferol production, calcium deficiency and hyperphosphatemia. Clinically, ROD occurs with varied manifestations – osteomalacia, osteoporosis, adynamic bone disease. The diagnosis and the treatment are a challenge for the physician and effort should be made to prolong the duration and quality of life of the affected patients.